The role of angiogenic factors in endometrial cancer - Żyła, Monika Magdalena; Kostrzewa, Marta; Litwińska, Ewelina; Szpakowski, Artur; Radosław Wilczyński, Jacek; Stetkiewicz, Tomasz (Menopause Review/Przegląd Menopauzalny, 2014)
Endometrial cancer is the most common malignancy within the female reproductive system (37.7%). The incidence increases with age. Frequently this type of cancer is diagnosed in peri- and post-menopausal women. 60-70% of cancers occur in women over 60 years of age, and less than 5% in women below 40 years of age. Angiogenesis is a process of formation of new microvessels from existing capillaries. There are four different mechanisms of new vessel growth: sprouting, intussusception, vessel elongation and incorporation of endothelial progenitor cells into new microvessels. Angiogenesis plays important roles in growth of endometrial cancers. This process is controlled by many angiogenic factors, for example vascular endothelial growth factor (VEGF). VEGF is the most powerful and most specific endothelial cell growth factor. It plays a crucial role in the initiation of physiological and pathological angiogenesis, lymphangiogenesis, and vasculogenesis. The VEGF family consists of VEGF-A, VEGF-B, VEGF-C, VEGF-D, VEGF-E, VEGF-F and PLGF (placental growth factor). The effects of VEGF are mediated through binding to the two specific and homologous receptors VEGFR-1 (FLT-1) and VEGFR-2 (KDR). Placental growth factor (PLGF) belongs to the VEGF family and it is also a very important growth factor. So far four isoforms of PLGF have been identified: PLGF-1 (PLGF131), PLGF-2 (PLGF152), PLGF-3 (PLGF203) and PLGF-4 (PLGF224).